(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
Parents are their children’s primary health decision makers, their knowledge towards immunization in general have a significant effect on the immunization status of their children. A descriptive (cross-sectional study) was conducted to assess parents’ knowledge toward immunization and its relation with pediatric immunization compliance at primary health care centers in Karbala city, Iraq A non-probability (convenience) sample of 292 parents selected from (5) primary health care centers. These centers distributed throughout (2) primary health care sectors selected randomly as (20%) from each sectors. The results of the present study indicated that the majority of studied parents had moderate level of knowledge, which was a significant associated with their age of fathers, level of education of father and mothers, occupational status of mothers, family type, , more than sixty present of studied parents have children partially immunized. In addition, the present study revealed that parents’ knowledge not had a significant influence on child’s immunization status. So, this study recommendedit is necessary to raise parents awareness of the importance of immunization by implementing educational programs and by traditional and social media with emphasis on time, side effects, contraindication, and disease preventable by immunization and promote periodically assessment for immunization coverage.